Depression in Patients with Tinnitus: A Systematic Review. (July 2019) - Salazar, James W.; Meisel, Karl; Smith, Eric R.; Quiggle, Aaron; McCoy, David B.; Amans, Matthew R.
Objective: Tinnitus is a condition that causes distress and impairment across cognitive, functional, and psychiatric spectra. In the psychiatric realm, tinnitus has long been associated with depression. To better characterize the co-occurrence of depression and tinnitus, we performed a systematic review of the prevalence of depression among patients with tinnitus. Data Sources: We comprehensively examined original studies reporting the prevalence of depression in adult populations with tinnitus, as indexed in the PubMed and Web of Science databases and published from January 2006 to August 2016. Review Methods: All identified articles were reviewed independently by 2 researchers, with a third reviewer for adjudication. Included studies were evaluated for threats to validity across 3 domains—representativeness, response rate, and ascertainment of outcome—on a 4-point modified Newcastle-Ottawa Quality Assessment Scale. Results: Twenty-eight studies were included, representing 15 countries and 9979 patients with tinnitus. Among the included studies, the median prevalence of depression was 33%, with an interquartile range of 19% to 49% and an overall range of 6% to 84%. Studies were high quality overall, with a mean score of 3.3 (SD = 0.76), and 89% utilized a validated tool to ascertain depression. Conclusions: We conducted one of the largest contemporary comprehensive reviews, which suggests a 33% prevalence of depression among patients with tinnitus. Our review reaffirms that a substantial proportion of patients with tinnitus have depression, and we recommend that all who treat tinnitus should screen and treat their patients for depression, if present.